Analisis Pelaksanaan Bimbingan Karir Dalam Menumbuhkan Kemampuan Siswa Memilih Sekolah Lanjutan - Fauzi, Taty; Nurbaiti, Nurbaiti (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2024)
This research aims to analyze the appropriateness and effectiveness of career guidance implementation in helping students choose between high school and vocational school. A quantitative descriptive approach was used, employing a one-group pretest-posttest design. The research involved a population of 186 students from SMP Negeri 33, with a randomly selected sample of 38 students. Data were collected using a questionnaire consisting of 25 items, which had been validated and tested for reliability. The data were analyzed using t-test statistics. The pretest scores indicated that the students' ability to choose a secondary school was in the sufficient category. Posttest scores showed significant improvement, placing the average in the good category. Statistical analysis confirmed that career guidance significantly enhanced students' ability to make informed decisions about their future education paths, as evidenced by the hypothesis test result (t_count > t_table). The implementation of career guidance was proven to be effective in developing students' ability to choose the appropriate secondary school, whether high school or vocational school.